1986
DOI: 10.1128/aac.29.4.579
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of itraconazole and fluconazole in treatment of cryptococcal meningitis and candida pyelonephritis in rabbits

Abstract: Itraconazole and fluconazole, two new triazoles, were examined for their antifungal activity in rabbits. Fluconazole easily crossed the blood-cerebrospinal fluid barrier, and active drug was eliminated in high concentrations in the urine. On the other hand, itraconazole did not cross the blood-cerebrospinal fluid barrier in measurable amounts, and urine concentrations were variable. Despite differences in pharmacokinetics at the site of infection, both agents were equally effective ill treating cryptococcal me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
93
1

Year Published

1988
1988
1995
1995

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(101 citation statements)
references
References 21 publications
7
93
1
Order By: Relevance
“…Nevertheless, for the best-documented strains clinically resistant to KZ, most results indicated that the strains were cross-resistant in vitro to other azoles (17,25,33). In vivo cross-resistance to azoles has also been described for some of these KZ-resistant C. albicans strains in experimental models of animal infection (26,33). With regard to the in vitro activity of IZ against C. albicans isolates with decreased susceptibility to FZ, our results are very similar to those of Barchiesi et al (3), who showed increased MICs of IZ for most but not all strains, although in the case of FZ-susceptible strains, the IZ MICs of Barchiesi et al (3) were lower than ours.…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, for the best-documented strains clinically resistant to KZ, most results indicated that the strains were cross-resistant in vitro to other azoles (17,25,33). In vivo cross-resistance to azoles has also been described for some of these KZ-resistant C. albicans strains in experimental models of animal infection (26,33). With regard to the in vitro activity of IZ against C. albicans isolates with decreased susceptibility to FZ, our results are very similar to those of Barchiesi et al (3), who showed increased MICs of IZ for most but not all strains, although in the case of FZ-susceptible strains, the IZ MICs of Barchiesi et al (3) were lower than ours.…”
Section: Discussionmentioning
confidence: 97%
“…In rabbits, fluconazole crossed the blood-brain barrier easily at 1 order of magnitude greater than that observed with other azole derivatives, i.e., ketoconazole, vibunazole, and itraconazole (215,216). Fluconazole is distinctive for its excellent cerebrospinal fluid penetration.…”
Section: Antifungal Imidazoles Under Developmentmentioning
confidence: 99%
“…One of these antifungal agents is the triazole fluconazole (Flu) (4,10,14,33,34,41). In vivo experimental studies suggested that Flu is active against disseminated candidiasis (8,9,29,31,32,35,37). Recently, the antifungal efficacy of Flu was demonstrated in persistently granulocytopenic rabbits when it was used for prevention or early treatment (39,40).…”
mentioning
confidence: 99%